A Source Effect Theory Perspective on How Opinion Leadership, Parasocial Relationship, and Credibility Influencers Affect Purchase Intention - Yudha, Aji (Jurnal Manajemen Teori dan Terapan| Journal of Theoretical and Applied Management, 2023)
Objective: Influencers are known to have a solid influence on generating purchase intentions in consumers. Therefore, this study aims to examine the effect of opinion leadership, parasocial relationships, and credibility identified through the variables of attractiveness, trust, and expertise on purchase intentions. Design/Methods/Approach: 206 individuals who follow food vlogger influencers were surveyed for this study. The data analysis was carried out using GSCA SEM with GSCA pro software, and the mediation test was conducted through the Sobel test. Findings: The results indicate that opinion leadership and parasocial relationships have a positive impact on purchase intention. In addition, attractiveness and trustworthiness can also influence purchase intention through parasocial relationships. However, it was observed that the expertise variable did not directly or indirectly affect purchase intention. Originality: In this study, variables are utilized based on source effect theory to facilitate the contribution of the results to the advancement of marketing theory and science, specifically in the field of influencer marketing. Practical/Policy implication: For marketers, selecting influencers who wield substantial influence over their audience and have forged robust relationships with them is crucial. These influencers are renowned for their opinion leadership and parasocial connections, making them ideal for promoting products or brands.